Characterization of multipod cadmium sulfide nanostructures synthesized by aminethermal method - Phuruangrat A. (2014)
Multipod (monopod, bipod, tripod and tetrapod) CdS nanostructures have been successfully synthesized under aminethermal method at 200 oC for 10 h without using any templates and surfactants. The product was characterized by X-ray diffraction (XRD), Raman spectroscopy, fast Fourier transformation (FFT), transmission electron microscopy (TEM), and high resolution TEM (HRTEM). XRD pattern shows wurtzite CdS structure. Its Raman spectrum respectively shows the LO1 and LO2 of A1 vibration mode at 300 and 601 cm-1, which are polarized in the x-z face, and strongly couple to the excitons along the c axis. The structures of multipod CdS were characterized using TEM and HRTEM.